Probing human proteins for short encrypted antimicrobial peptides reveals Hs10, a peptide with selective activity for gram-negative bacteria - Santos, Michele A.; Silva, Fernanda L.; Lira, Bianca O.V.; Cardozo Fh, José L.; Vasconcelos, Andreanne G.; Araujo, Alyne R.; Murad, André M.; Garay, Aisel V.; Freitas, Sonia M.; Leite, José Roberto S.A.; Bloch, Carlos; Ramada, Marcelo H.S.; et al. (Biochimica et biophysica acta. General subjects, 2023)
Some cationic and amphiphilic α-helical segments of proteins adsorb to prokaryotic membranes when synthesized as individual polypeptide sequences, resulting in broad and potent antimicrobial activity. However, amphiphilicity, a determinant physicochemical property for peptide-membrane interactions, can also be observed in some β-sheets. The software Kamal was used to scan the human reference proteome for short (7–11 amino acid residues) cationic and amphiphilic protein segments with the characteristic periodicity of β-sheets. Some of the uncovered peptides were chemically synthesized, and antimicrobial assays were conducted. Biophysical techniques were used to probe the molecular interaction of one peptide with phospholipid vesicles, lipopolysaccharides (LPS) and the bacterium Escherichia coli. Thousands of compatible segments were found in human proteins, five were synthesized, and three presented antimicrobial activity in the micromolar range. Hs10, a nonapeptide fragment of the Complement C3 protein, could inhibit only the growth of tested Gram-negative microorganisms, presenting also little cytotoxicity to human fibroblasts. Hs10 interacted with LPS while transitioning from an unstructured segment to a β-sheet and increased the hydrodynamic radius of LPS particles. This peptide also promoted morphological alterations in E. coli cells. Conclusions: Data presented herein introduce yet another molecular template to probe proteins in search for encrypted membrane-active segments and demonstrates that, using this approach, short peptides with low cytotoxicity and high selectivity to prokaryotic cells might be obtained. This work widens the biotechnological potential of the human proteome as a source of antimicrobial peptides with application in human health. •Human proteome was mined for cationic and amphiphilic segments with β-sheet periodicity.•Some segments were synthesized and tested, with MICs in micromolar scale.•One peptide, Hs10, inhibited only Gram-negative bacteria, with little cytotoxicity.•LPS was characterized as a relevant binding partner for Hs10.•Cationic and amphiphilic β-sheets encrypted in human proteins serve as antibiotics.